Smoke-free policy development in Italy through the legislative process of the ban 2000-2005, and press media review 1998-2008 - Giuseppe Gorini; Laura Currie; Lorenzo Spizzichino; Daniela Galeone; Maria J. Lopez (Istituto Superiore di Sanità, 2011)
The objective of this article is to describe the process of approval of the Italian smoking ban, enacted in 2005. The method is to conduct a review of proposed and approved legislation 20002005, and of articles published in Italian newspapers, 1998-2008. Enabling factors in the process were: the leadership of two consecutive Health Ministers, both physicians, who introduced the bill four times between 2000-2002; the repeated presentation and final approval of the bill as an amendment within a bill on public administration which enabled timely approval of the ban; and the stringent air quality standards in the 2003 regulation that made building smoking rooms impracticable and prohibitively expensive. Limiting factors in the process were: the 6-month delay in approving the regulation on smoking rooms; the 1.5-year delay in approving the regulation establishing owners' responsibility for enforcing the ban in hospitality premises and the legal action in August 2005, which shifted responsibility for enforcement to police. Eighty-three percent of the 808 articles published on smoking in 1998-2008 were released between 2000-2005, during the policy process. While the press devoted considerable attention to the issues raised by the hospitality sector, the long legislative process of the bill and its regulations also stimulated coverage on tobacco control issues.